EXPLORATION AND IDENTIFICATION OF MICROBES AND FUNGI FROM SOIL SAMPLES OF GUNGGUNG VILLAGE, BATUAN DISTRICT, SUMENEP REGENCY AS BIOLOGICAL CONTROL AGENTS AT THE EAST JAVA FOOD CROPS AND HORTICULTURE PLANT PROTECTION LABORATORY - Anindita Darma, Diva; Misnati Nur Indahsari, Wiwin (Universitas Cokroaminoto Palopo, 2026)
Soil microorganisms play an essential role in maintaining soil fertility and suppressing plant pathogens, making them potential biological control agents in sustainable agriculture. This study aimed to explore and identify microbes and fungi from soil samples collected from yellow Kepok banana (Musa spp.) plantations in Gunggung Village, Batuan District, Sumenep Regency, as potential biological agents. The novelty of this research lies in the exploration of untreated Fusarium-infected banana plantation soil to obtain indigenous microbial isolates with biocontrol potential. A descriptive exploratory research design was employed. Bacterial isolation was conducted using the serial dilution method on Potato Dextrose Agar (PDA), followed by purification, macroscopic and microscopic characterization, 5% KOH test, soft rot test, and hypersensitivity test. Fungal isolation was performed using the baiting method with coconut, rice, and mealworms as substrates, followed by morphological identification. The results revealed the presence of Bacillus sp. as the dominant bacterial isolate, characterized by circular colonies, yellowish-white color, Gram-positive reaction, and rod-shaped cells. Soft rot and hypersensitivity assays indicated varying pathogenic responses among isolates. Fungal identification showed the presence of Aspergillus sp. (brownish-green, powdery colonies) and Penicillium sp. (yellowish-green, granular colonies). These findings indicate that soil from the study site contains microbial populations with potential applications as biological control agents. The study highlights the importance of exploring indigenous soil microorganisms to support environmentally friendly plant disease management and sustainable agricultural practices.